Nanoparticle-Based Drug Delivery in Cancer Therapy and Its Role in Overcoming Drug Resistance - Yao, Yihan; Zhou, Yunxiang; Liu, Lihong; Xu, Yanyan; Chen, Qiang; Wang, Yali; Wu, Shijie; Deng, Yongchuan; Zhang, Jianmin; Shao, Anwen (Frontiers in Molecular Biosciences, 2020)
Nanotechnology has been extensively studied and exploited for cancer treatment as the important role of nanoparticles in drug delivery system. Compared with conventional drugs, nanoparticle-based drug delivery has specific advantages, including good stability, biocompatibility, enhancing permeability and retention effect and precise targeting. In addition, nanoparticle drugs have also shown a certain role in overcoming drug resistance of cancer. The application and development of hybrid nanoparticles with combined properties of different nanoparticles lead this type of drug-carrier system to a further step. In this review, we discuss the nanoparticles and hybrid nanoparticles for drug delivery, and describe the targeting mechanism of nanoparticle-based drug delivery as well as its function on reversing drug resistance.